Safety, Pharmacokinetics, and Antiviral Activity of a Novel HIV Antiviral, ABX464, in Treatment-Naive HIV-Infected Subjects in a Phase 2 Randomized, Controlled Study - Steens, Jean-Marc (Antimicrob Agents Chemother, 2017)
We investigated the safety and antiviral effects of an anti-HIV compound (ABX464) with a unique mechanism of viral replication inhibition. This was a randomized, double-blind, placebo-controlled, dose-ranging study in treatment-naive HIV-infected patients. Participants were assigned to eight groups; each group included eight subjects receiving either the study compound, ABX464 (n = 6), or the corresponding placebo (n = 2), according to a randomization code. The first dose administered was 25 mg, given once or 3 times a day over a 2- to 3-week period. Ascending doses of up to 150 mg were delivered after review of the safety data. The primary objective of the study was to assess the safety and tolerability of ABX464 after repeated oral administrations in subjects infected by HIV. Sixty-six subjects were enrolled and were randomized. Sixty-three subjects completed the study according to the study protocol. Twenty-one adverse events (AEs) were reported by 7 subjects out of 16 (44%) who received placebo, and 158 AEs were reported by 39 subjects out of 50 (78%) who received the study drug. In the ABX464 treatment group, all of these adverse events were mild to moderate. No subjects discontinued treatment due to drug-related AEs. Administration of ABX464 at up to 150 mg once a day was safe and well tolerated in HIV-infected subjects. An efficacy signal with respect to a reduction of the viral load by ABX464 was detected, mainly in subjects treated at the highest dose. Further studies will be required to demonstrate antiviral effects in HIV-infected subjects in combination with other antiretroviral therapies. (This study is registered on the ClinicalTrials.gov website under registration no. NCT02452242.)